Politics of Law on the State Control of Oil and Gas in Indonesia: Gas Liberalization and the Hesitancy of Constitutional Court - Zain, Mochamad Adib (Faculty of Law, Universitas Negeri Semarang, 2016)
This study aims to examine in depth the legal political state control over oil and gas in Indonesia. This research is a normative law by secondary law. Based on the research can be argued that the existence of Act No. 22 of 2001 on Oil and Gas can’t be separated from other state intervention. The substance oil and gas law dictation by IMF and USAID. Consequently oil and gas law is characterized by a liberal. It eliminates the mean of state control over oil and gas in Indonesia. The Constitutional Court as a judicial institution that is given the authority to judicial review of the constitution less did his part well. The Constitutional Court only eliminated some arrangements liberalization in the Act.